1159 Ring-Fenced Arthroplasty Unit: The Need of The Hour During Winter and A Pandemic Crisis. (12th October 2021) - Srikumar, B; Perianayagam, G R; Narayan, P; Pawar, R; Antapur, P
Abstract: Aim: Winter pressures along with the COVID-19 pandemic, have caused cancellation of elective services, prolonged waiting times, patient dissatisfaction and financial implications. Length of stay (LOS) following joint replacements is variable. The availability of ring-fenced beds and enhanced recovery protocol (ERP) can improve these outcomes. The performance of a stand-alone arthroplasty unit in an acute NHS Trust was assessed regarding safety, LOS and complications. Method: Patient data was collected for total hip & knee replacements (TJAs) between the months of December to March of 2018-19 and 2019-20. Demographics, ASA, transfusion rates, LOS and 90-day reattendance was analysed. Modified ERP implemented in late 2019 included changes in analgesia and early post-operative mobilisation. The performance was then compared with DGHs within the region. Results: In 2019-20, of 280 TJAs performed, there was a mean LOS of 43 hours. This shows a reduction compared with LOS of 69 hours in 2018-19, where 288 TJAs were performed. In 2019-20, 74% of cases had early discharge within 36 hours of surgery, versus 24% in 2018-19. This accumulates to 333 inpatient days saved. Note that following ERP modification, 6 patients were discharged on the day of surgery. Surgery related complications within 3 months which required reattendance, were seen in only 2 patients. This unit performed an average of 335 TJA's in these winter months, the highest average in comparison to other DGHs in the East Midlands region, which had an overall average of 165 cases. Conclusions: A ring-fenced arthroplasty service with adherence to ERP significantly decreases LOS and increases productivity.